Variability of annual polar motion and its relationship to the Chandler wobble - Songyun Wang; Clark R. Wilson; Jianli Chen; Ki-Weon Seo; Yuning Fu; Weijia Kuang (Proceedings of the National Academy of Sciences, 2025)
Given the large amplitude of prograde annual polar motion, we are able to quantify year-to-year variability of prograde annual excitation amplitude since pre-1900 observations. We obtain a Prograde Annual Amplitude Modulation (PAAM) time series and use it to investigate several key topics, including variability in annual excitation amplitude, its climatic sources, and its potential role in Chandler wobble (CW) excitation. An important finding is that the PAAM series undergoes multiyear episodes of a near six-year oscillation (SYO). This provides observational evidence for a SYO in Earth’s climate and rotational dynamics seen in recent data and confirms SYO behavior in the climate system over the past century. Using climate model and other data, we find that several fluid components of Earth’s climate system contribute to the SYO, with atmospheric sources playing the dominant role. A SYO [~0.16 cycles per year (cpy)] modulation of the annual component introduces variations at the sum and difference frequencies (1 + 0.16 cpy and 1 − 0.16 cpy). Because the difference frequency 0.84 cpy is near the Chandler frequency, the SYO may be important in understanding CW excitation. Our results show the SYO contributes significantly to the excitation of CW. Year-to-year variability of the annual excitation was originally proposed as an excitation mechanism by Harold Jeffreys in 1940, and we confirm that more than half the CW excitation power can be attributed to this cause. We also found annual excitation modulation at a period near 17 mo (~0.7 cpy) that is a source of excitation power near 1 ± 0.7 cpy.